High-altitude acclimatization improves recovery from muscle fatigue - Ruggiero, L.; Hoiland, R. L.; Hansen, A. B.; Ainslie, P. N.; McNeil, C. J. (Medicine & Science in Sports & Exercise, 2020)
PURPOSE: